Catalytic C‐2 Allylation of Indoles by Electronic Modulation of the Indole Ring and its Application to the Synthesis of Functionalized Carbazoles. Issue 21 (30th September 2016) - Lee, Ju Young; Ha, Hyeri; Bae, Seri; Han, Inhyuk; Joo, Jung Min
Abstract: We report a palladium‐catalyzed C‐2 allylation of indoles and subsequent cyclization of the allylated indoles. The electronic effects of chloro and ester groups that can be readily installed at the C‐3 position of indoles facilitated a highly efficient C–H allylation at the C‐2 position. The resulting 2‐allyl‐3‐chloroindoles were found to be suitable substrates for benzannulation reactions with alkynes and norbornadiene as an acetylene synthon. This approach, utilizing readily available indoles, allyl acetates, and norbornadiene, allows a rapid access to complex carbazoles. Abstract :